Enteral nutrition in end of life care: The Jewish Halachic ethics - Greenberger, Chaya (Nursing ethics, 2015)
Providing versus foregoing enteral nutrition is a central issue in end-of-life care, affecting patients, families, nurses, and other health professionals. The aim of this article is to examine Jewish ethical perspectives on nourishing the dying and to analyze their implications for nursing practice, education, and research. Jewish ethics is based on religious law, called Halacha. Many Halachic scholars perceive withholding nourishment in end of life, even enterally, as hastening death. This reflects the divide they perceive between allowing a fatal disease to naturally run its course until an individual’s vitality (life force or viability) is lost versus withholding nourishment for the vitality that still remains. The latter they maintain introduces a new cause of death. Nevertheless, coercing an individual to accept enteral nourishment is generally considered undignified and counterproductive. A minority of Halachic scholars classify withholding enteral nutrition as refraining from prolonging life, permitted under certain circumstances, especially in situations where nutritional problems flow directly from a fatal pathology. In the very final stages of dying, moreover, there is a general consensus that enteral nourishment may be withheld, providing that this reflects the dying individuals’ wishes. In the event of enteral nourishment becoming a source of overwhelming discomfort, two Halachic ethical mandates would come into conflict: sustaining life by providing nourishment and alleviating suffering. As in all moral conflicts, these would have to be resolved in practice. This article presents the issue of enteral nourishment as it unfolds in Halacha in comparison to secular and other religious perspectives. It is meant to serve as a foundation for nurses to reflect on their own practice and to explore the implications for nursing practice, education, and research. In a world that remains broadly religious, it is important to sensitize health practitioners to the similarities and differences among religions and between secular and religious approaches to ethical issues.